Quantitative magnetic resonance imaging responses in head and neck cancer patients treated with magnetic resonance-guided hypofractionated radiation therapy - Ryan Bonate; Musaddiq J. Awan; Heather A. Himburg; Stuart Wong; Monica Shukla; Sergey Tarima; Joseph Zenga; Eric S. Paulson (Physics and Imaging in Radiation Oncology)
Background and purpose: Quantitative MRI (qMRI) has been explored for detecting tumor changes during radiation therapy (RT) in head and neck squamous cell cancer (HNSCC). Clinical trials show prolonged survival with PD-1 targeted immune checkpoint inhibition. Hypofractionated radiation regimens are being studied to counteract radioresistant clonogen formation. This study aims to use daily qMRI monitoring in these therapies. The objective of this exploratory study was to investigate if qMRI can detect tumor microenvironment changes during hypofractionated RT in a phase I trial of Dose-Escalated Hypofractionated Adaptive Radiotherapy (DEHART). Materials and methods: Seventeen subjects with advanced HNSCC underwent MR-guided RT with daily qMRI using a 15-fraction regimen to a cumulative dose of 50, 55, or 60 Gy. A 1.5 T MRI-Linac collected daily intravoxel incoherent motion (IVIM), T1, and T2 mappings. Median primary tumor ADC, D, D*, f, T1, and T2 were calculated, using paraspinal muscle as a control. qMRI parameters were analyzed by treatment condition and length using linear mixed effect models and nonparametric tests. Results: Significant (p < 0.05) increases in ADC, D, f, and T2 were observed over treatment duration for multiple conditions. Daily monitoring enhanced result significance compared to weekly collection. Conclusions: Daily qMRI effectively monitors tumor response over short periods and varying treatment conditions. Further studies on radiation and systemic therapy combinations in HNSCC could benefit from daily qMRI data collection.